The Influence of ENSO/IOD on SST Signal in Kendari, Southeast Sulawesi Waters: 27-year-records of Sr/Ca from Porites corals - Sri Yudawati Cahyarini; Suharsono Suharsono (Indonesian Journal on Geoscience, 2015)
DOI:10.17014/ijog.2.1.43-51Indonesia is an interesting and important location for a climate study, because it is located in the centre of a warm pool and adjacent to Pacific and Indian Oceans. Long records of climate data are required from this region to more understand the climate variability and the response of global warming. Geochemical proxies derived from Porites corals are believed to be an excellent climate recorder. Sr/Ca content in Porites corals from Kendari, Southeast Sulawesi shows that seasonal variability of SST is resolved by coral Sr/Ca from this region. The monsoon strongly influences reconstructed SST from coral Sr/Ca. Coral SST shows strong power spectrum at the 2.75 year period. Annual to interannual coral SST signal is stronger than the decadal to interdecadal signal. Both ENSO and IOD influence coral SST at two-month and three-month lags respectively.